The flavonoid rutin protects against imidacloprid-induced osmotic and electric disruptions in Africanized honey bees - Juan P. Hernández; Fredy Mesa; Andre J. Riveros (PLoS ONE, 2025)
Honey bees (Apis mellifera) are essential pollinators threatened by sublethal effects of pesticides such as imidacloprid, a widely used neonicotinoid that disrupts the central nervous system. However, many of the systemic effects are poorly understood, especially on the physiological homeostasis of the honey bee. We evaluated the effects of oral administration of imidacloprid and the flavonol rutin on the properties of extracellular fluid (ECF) in Apis mellifera. We measured water content, evaporation rate, electrical impedance, and ion mobility of the ECF. Our results show impacts of imidacloprid consumption, such as water content decrease, slowed evaporation, and altered electrical characteristics of the thorax segment. All these events suggest disruption of osmotic and electrochemical balance. Particularly, the rutin consumption partially mitigated the imidacloprid effects in a dose-dependent manner, enhancing detoxification. Our results point out that imidacloprid alters ionic and osmotic homeostasis beyond neural targets; and on the other hand, rutin may protect against these disruptions through physiological mechanisms beyond neuroprotection. These findings highlight new alternatives and evaluations for protecting pollinators via dietary strategies.